Superovulation in different buffalo genotypes - Situmorang, Polmer (Indonesian Animal Sciences Society, 2003)
Studies has been conducted to evaluate the response of different buffaloes genotype to superovulation treatments. PSMG (2500 IU) was injected intra muscular in a single injection on day 10 of estrus cycle while a total of 12 ml Folltropin was administrated twice a day with 12 hours interval in a decreasing doses for 4 days (2.5; 2.5; 2.0; 2.0; 1.0; 1.0 and 0.5; 0.5 ml). Embryos were collected by non-surgically technique on day 6 of estrus cycle by flushing each horn of uterus with 500 ml Dubelcos Phosphat Buffer Saline (DBPS). Diameter of ovary (DO), total corpora lutea (TCL), total embryo (TE) and percentage of recovery rate (% RR) were recorded as parameters. Administration of hormone highly significantly (P<0.01) affected the ovulation response of buffalo. The mean DO was highly significantly higher (P<0.01) in PMSG than that in Folltropin (9.5 vs 4.4 cm), but TCL, TE and % RR were significantly lower (P<0.01) in PMSG (2.0; 0.0 and 0.0 vs 5.5; 2.6 and 43.7). The mean DO was significantly higher (P<0.05) in river than both in swamp and crosses (6.0 vs 4.3 and 3.3 cm). No significantly differentwas observed between the mean DO of swamp and crosses. TCL, TE and % RR were not statistically significant among different buffalo genotype. The mean of TCL, TE and % RR were 6.2, 2.5 and 48.0; 5.8; 2.3 and 40.0 and 5.7; 3.3 and 52.8 for river, swamp and crosses buffalo, respectively. Both left and right ovary gave a similar response to superovulation treatments. In onclusion, the response of a different buffalo genotypes following superovulation with Folltropin was not significant.Â Key words: Superovulation, buffalo, genotype, embryo